PENGARUH VARIABEL TEKANAN DAN WAKTU TERHADAP RANDEMEN MINYAK JARAK PADA PROSES PEMERAHAN DENGAN MENGGUNAKAN MESIN PRESS HYDROLIK - , Sugeng Riyadi, Drs, Ir. Agus Prasetya, M.Eng.,Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to explore the influence of Hydraulic pressure and the duration of the pressure toward yield of Jatropha curcas oil which is resulted by the process of taking the Jatropha curcas oil by using Hydraulic press method. The method of this research is complete random design plan (CRP) which is consist of two treatment factors they are first the pressure factor, which consists of five variation, they are : 56, 49 Kg/cm², 112,97 Kg/cm², 169,46 Kg/cm², 225,94 Kg/cm², 282,43 Kg/cm², and 338,91 Kg/cm². Second, the pressing duration factor, which consists of ten variations, which has different variation of the intervals, which is from 2 seconds up to 20 seconds with the same duration of interval, that is 2 second. It will be gained the data from those factor about 60 sample with 23 times repetition, so that it will be gaineds about 180 sample. The parameter of this research is yield. The data analysis technique of this research will by using SPSS r 15 (statistical product and service solution). The result of this research is that the Hydraulic pressure and the duration of the pressing affect the yield of resulted oil. The correlation between yield, pressure and pressing duration can be explained by the formula R = 12,981 + 0,249 t + 0,052 P, which requires t and P is not equal to 0 (zero) or t and P > 0. Based on the result of the experiment it can be explained that R is yield of the result oil, while t is the duration of pressing, and P is the volume of pressing power in Kg/cm²